Blind gastric biopsy in the diagnosis of Helicobacter Pylori infection - Meral AKDOĞAN,; Ali MERT,; Süha GÖKSEL,; Recep ÖZTÜRK,; Sebati ÖZDEMİR,; Abdullah SONSUZ,; Hakan ŞENTÜRK, (Turkish Journal of Gastroenterology, 2019)
-